Numerical modelling technique for predicting the seismic fault zone (SFZ) in the earthquakes affected area, NW Himalayas with its neotectonic implication - Howladar, M Farhad; Afroz, Sharmin; Islam, Shofiqul (Journal of Life and Earth Science, 2011)
Finite elements analysis is a powerful tool, often used for analyzing problems on stress, that can be successfully employed to analyze the finite deformation of geological structures in a mathematical form on a digital computer. Over the last century, great earthquakes with magnitudes of 7->8 have struck in the NW Himalaya; the 1905 Kangra earthquake is one of them. This study performed a plane strain analysis of failure stress and faults in these earthquakes potential region based on the seismic geologic cross profile employing the two-dimensional finite element method under elastic material state with Mohr Coulomb failure criterion. The results show that the normal fault initiates at deeper level, whereas with increasing convergent displacement the thrust fault appears in the shallower region. The results of the simulation are compared with the available seismic and earthquakes focal mechanism solution data of the area which shows the close similarities between the distribution of simulated fault and microseismicity in the deeper region of Chamba Nappe (CN) and along the upper part of the Mid Crustal Ramp (MCR) which might be the Seismic Fault Zone (SFZ) of the region. Moreover, the intense localization of faults along the frontal part of the model indicates that this part is active in nature at present, which is responsible for the neotectonics in the Himalayas. Keywords: NW Himalaya; numerical technique; seismic fault zone; neotectonics DOI: 10.3329/jles.v2i2.7499 J. Life Earth Sci., Vol. 2(2) 57-65, 2007